Ética do cuidado e empatia: em defesa de uma metaética sentimentalista para os direitos humanos - Gonçalcves, Roberta Candeia (2012)
This dissertation presents the ethics of care that currently operates through the use of empathy as a tool for recognition and moral motivation. The goal is to strive for theoretical consistency of care ethics as an alternative carried out by an ethical review of human rights, since it generates more robust results regarding the effectiveness of their prescriptions, within the theory of moral action. The methods used for the making of the work are, concurrently, the deductive method of theoretical approach, with the aim to verify the conclusions of the argumentative analysis of this metaethical theory find satisfactory answer to the problems previously identified and, then, that the level criticism of some of their claims lay the foundations of this theory, the same way as the dialectical method to justify the adoption of this new theory instead of the current one, which act as a parameter of formulation with logical-argumentative resolute purpose. The present study consists of four (04) chapters, the first being the introduction, besides conclusion. The second chapter presents the theoretical and philosophical foundations of contemporary ethics of care, from sentimentality and ethical emotivism, in addition to the ethics of care seminal feminist theory. The third one outlines the fundaments of some theoretical misconceptions in Kantian rationality, especially the so-called moral cleansing process that seeks to promote the unity of reason. The fourth chapter draws up a conceptual attempt to empathize and outlined the main arguments of the empathy-based ethics of care, etched categories by analyzing some authors present the philosophy and moral psychology. Finally, I conclude that it is possible the theoretical underpinning of care ethics from empathy as well as possible and be more advisable to apply this theory as a basis and instrument of Human Rights instead of the actual Kantian ethics, since it brings together most successfully moral judgments and the subsequent action according to their requirements. I propose feelings as non-textual elements of human rights and therefore the urgent need for an education in/ for human rights also as a sentimental education. Other issues concerning the validity of ethics of care and empathy remain open in the final, which highlights the importance for further investigation of this theory under the realm of Law.